(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The profound social transformations, the increase in interpersonal violence in a public space, including workplaces and learning places, the media coverage of sexual scandals (such as the famous “Harvey Weinstein” case), and the response to these problems (#MeToo, #balancetonporc on Twitter, #Iwas), urgently raise the problem of their collective representation today and what forms of degradation the male-female relationship is likely to have. To address the topic of harassment, we divide the treatment as follows: 1) Methodological premise; 2) what is harassment; 3) the forms of harassment; 4) what psychology and sociology can tell us about the phenomenon in question; 5) domestic violence; 6) Defense against harassment.